QUANTITY AND QUALITY OF BREAKFAST OF CHILDREN AGED 2.0 TO 12.9 YEARS IN INDONESIA - Harahap, Heryudarini; Widodo, Yekti; Sandjaja, Sandjaja; Khouw, Ilse; Deurenberg, Paul (PERSATUAN AHLI GIZI INDONESIA, 2019)
Doing breakfast among children is a public health concern as seen at one of the messages in ?Indonesian balanced nutrition which state ?breakfast every day?. The aim of this analysis is to determine the quantity and quality of Indonesian children?s breakfast based on children and parent characteristics, as well as nutritional status. Subjects were 2629 children, aged 2.0?12.9 years, included in the Southeast Asian Nutrition Study. The amount of the breakfast is categorized as very inadequate if <15 percent; inadequate if 15 to < 25 percent; or adequate if ? 25 percent of the Indonesian RDA. The quality of breakfast was categorized as ?not good?, if the breakfast skips one or more components of energy, protein and/or vitamins/minerals, or ?good? if the breakfast provides energy, protein and vitamins/minerals. The results indicated that on average only 31.6 percent of the children were categorized as having adequate breakfast consumption and 21.6 percent having good quality breakfast. Only 9.2 percent of children have adequate and good quality breakfast. Adequacy of breakfast differed between children, parent characteristics, and nutritional status, but only age has an association with the quality of breakfast (p<0.05). The nutrition education about good breakfast should be included as the part of curriculum, and school canteens provided a good food, as well as a campaign about Indonesian balanced nutrition slogan number 1 ?have breakfast every day? should be socialized.